2019
DOI: 10.1182/bloodadvances.2019000201
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and feasibility of virus-specific T cells derived from umbilical cord blood in cord blood transplant recipients

Abstract: Adoptive transfer of virus-specific T cells (VSTs) has been shown to be safe and effective in stem cell transplant recipients. However, the lack of virus-experienced T cells in donor cord blood (CB) has prevented the development of ex vivo expanded donor-derived VSTs for recipients of this stem cell source. Here we evaluated the feasibility and safety of ex vivo expansion of CB T cells from the 20% fraction of the CB unit in pediatric patients receiving a single CB transplant (CBT). In 2 clinical trials conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
(54 reference statements)
0
34
0
Order By: Relevance
“…However, third party donors are now being used to create banks for off-the-shelf products for immediate use [78]. There is a theoretical concern about graft versus host disease due to HLA mismatches from third party products; however, the reported rate has been low so far in published studies [79][80][81][82][83][84]. Table 2 groups in the setting of randomized controlled trials.…”
Section: Adoptive T Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, third party donors are now being used to create banks for off-the-shelf products for immediate use [78]. There is a theoretical concern about graft versus host disease due to HLA mismatches from third party products; however, the reported rate has been low so far in published studies [79][80][81][82][83][84]. Table 2 groups in the setting of randomized controlled trials.…”
Section: Adoptive T Cell Therapymentioning
confidence: 99%
“…These were not restored in the 5 patients who did not clear CMV. Abraham et al 2019 [ 83 ] Cord blood derived virus-specific T cells 14 Allo-SCT patients who received cells for prophylaxis and infection. 7 patients who received prophylaxis did not develop reactivation.…”
Section: Adoptive T Cell Therapymentioning
confidence: 99%
“…Heslop et al showed that ex vivo expanded, donor-derived, EBV-specific, polyclonal T cells, expressing an effector memory phenotype, persisted for as long as 12.5 years post-infusion [49] and provided persistent activity against viral reactivation with no evidence of monoclonal outgrowth. Other groups also have demonstrated long-term presence of polyclonal, donor-derived, single-or multivirus-specific T cells after adoptive transfer [52,109] or stable remission over the years of patients with refractory PTLD receiving EBV-specific T cells [110]. Notably, even in third-party settings, off-the-shelf, partially HLA-matched VSTs persisted up to 12 weeks following infusion, offering durable benefits [86,87], or provided up to 12 months control of previously refractory CMV infections in the majority of treated patients [111].…”
Section: Long-lasting Immunitymentioning
confidence: 99%
“…Eighteen out of twenty-one products were successfully manufactured for clinical use and administered products were shown to confer antiviral immunity and/or complement pharmacotherapies. Obstacles still remain in terms of manufacturing times and yield, which is currently being assessed in a follow up clinical trial (NCT03594981) (59).…”
Section: Cord Blood-derived Third Party Vstmentioning
confidence: 99%